Quantitative characterization of the interfacial adhesion of Ni thin film on steel substrate: a compression-induced buckling delamination test - Zhu, W.; Zhou, Y.; Guo, J.; Yang, L.; Lu, Chunsheng (Pergamon, 2015)
A compression-induced buckling delamination test is employed to quantitatively characterize the interfacial adhesion of Ni thin film on steel substrate. It is shown that buckles initiate from edge flaws and surface morphologies exhibit symmetric, half-penny shapes. Taking the elastoplasticity of film and substrate into account, a three-dimensional finite element model for an edge flaw with the finite size is established to simulate the evolution of energy release rates and phase angles in the process of interfacial buckling-driven delamination. The results show that delamination propagates along both the straight side and curved front. The mode II delamination plays a dominant role in the process with a straight side whilst the curved front experiences almost the pure mode I. Based on the results of finite element analysis, a numerical model is developed to evaluate the interfacial energy release rate, which is in the range of 250–315 J/m2 with the corresponding phase angle from -41° to -66°. These results are in agreement with the available values determined by other testing methods, which confirms the effectiveness of the numerical model.